2019
DOI: 10.1002/chem.201903496
|View full text |Cite
|
Sign up to set email alerts
|

Toehold‐Mediated Strand Displacement in a Triplex Forming Nucleic Acid Clamp for Reversible Regulation of Polymerase Activity and Protein Expression

Abstract: Triplex forming oligonucleotides are used as a tool for gene regulation and in DNA nanotechnology. By incorporating artificial nucleica cids, target affinity and biological stabilitys uperior to that of naturalD NA mayb e obtained. This work demonstrates how ac himeric clamp consisting of acyclic( L)-threoninol nucleic acid (aTNA) and DNA can bind DNA and RNA by the formationof ah ighly stable triplex structure. The (L)-aTNA clamp is released from the targeta gain by the addition of ar eleasing strand in as tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Finally, the approach is also relevant for RNA sequences that can form triplex structures in a similar way to DNA sequences (Figure S8). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the approach is also relevant for RNA sequences that can form triplex structures in a similar way to DNA sequences (Figure S8). …”
Section: Resultsmentioning
confidence: 99%
“…were the first to report on the synthesis of aTNA and that aTNA forms an antiparallel homo‐duplex of high stability [17, 18] . We have later shown that aTNA forms highly stable sandwich type triplex structures with DNA and RNA and that aTNA is capable of forming i‐motifs and G‐quadruplexes [19–22] . This artificial oligonucleotide furthermore forms parallel duplexes with DNA and RNA, presumably because of an optimal rigidity [17] .…”
Section: Figurementioning
confidence: 95%
“…The triplex formation phenomenon has been used for reversible regulation of polymerase activity and protein expression [61]. It was found that a construct of two acyclic L-aTNA homopyrimidine segments (linked to a hexaethylene glycol linker) and DNA (directly linked to an L-aTNA segment) can bind DNA and RNA by forming a highly stable triplex structure.…”
Section: Threoninol Nucleic Acids (Tna)mentioning
confidence: 99%